2016
DOI: 10.1016/j.jinf.2016.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for pneumonia development and progression to respiratory failure in MERS-CoV infected patients

Abstract: For successful control of MERS outbreak, MERS-CoV infected patients with ≥ two predictive factors should be intensively managed from the initial presentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
125
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(139 citation statements)
references
References 31 publications
13
125
1
Order By: Relevance
“…In addition, out study demonstrated that patients' age and comorbidity did not differ significantly between intubation and nonintubation groups in patients with MERS pneumonia. These results are in contrast with the previous reports, including one by Das et al, which suggested that geriatric immunocompromised patients with MERS are at higher risk of fatal outcomes [15][16][17][18]. We found out that development of MERS pneumonia, rather than final outcome, was more frequently noted in patients with comorbidities.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In addition, out study demonstrated that patients' age and comorbidity did not differ significantly between intubation and nonintubation groups in patients with MERS pneumonia. These results are in contrast with the previous reports, including one by Das et al, which suggested that geriatric immunocompromised patients with MERS are at higher risk of fatal outcomes [15][16][17][18]. We found out that development of MERS pneumonia, rather than final outcome, was more frequently noted in patients with comorbidities.…”
Section: Discussioncontrasting
confidence: 99%
“…One of the unique issues of Korean MERS outbreak is the so-called, super-spreaders, who resulted in extremely high human-to-human transmission rate. A total of 136 cases (73.1%) among 186 MERS patients of Korean outbreak, were actually transmitted from only three patients [8,18]. A recent report by Ko et al, specified the presence of radiographic abnormality, indicating MERS pneumonia in all three patients suspected of super spreading the infection [18].…”
Section: Discussionmentioning
confidence: 99%
“…The patients with at least two, one and none of the predictive pneumonia factors developed pneumonia in 100%, 50% and 0% of cases, respectively [61].…”
Section: Risk Factors For Severe Mersmentioning
confidence: 99%
“…The three most frequent symptoms are: fever (77% [IQR: 59-82]), cough (90% [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69]), and dyspnea (68% ).…”
Section: Clinical Symptomsmentioning
confidence: 99%
“…4 Multiple health care−associated outbreaks were described mainly in the Kingdom of Saudi Arabia 5,6 and 1 large outbreak in South Korea spanning >17 health care settings. 7,8 In a systematic screening of all admitted patients with community-acquired pneumonia to a hospital in Saudi Arabia, only 20 (0.74%) of 2,657 screened patients were positive for MERS-CoV by polymerase chain reaction testing. 9 The spectrum of MERS-CoV infection ranges from mild to severe and fulminant infections with severe acute respiratory disease.…”
mentioning
confidence: 99%